РОЗРАХУНОК ПРОЦЕСІВ У ПЕРЕТВОРЮВАЧІ ЗІ ЗМЕНШЕНОЮ ПУЛЬСАЦІЄЮ ВИХІДНОЇ ПОСТІЙНОЇ НАПРУГИ - Руденко, Ю.В. (Інститут електродинаміки Національної академії наук України, 2023)
The electromagnetic processes in elementary dc converter according to the Luo topology with inverting output in  modes of continuous and discontinuous conduction were studied. Using the method of averaging in the state space based on Lagrange theorems, mathematical models of converter for mentioned modes of operation have been developed. The use of developed models made it possible to obtain analytical expressions for calculating the average and pulsation values ​​of currents and voltages in the reactive elements of the converter, as well as their ripple coefficients. Graphical dependences of the mentioned parameters were calculated in the entire commutation range of converter, taking into account the conduction modes. It is shown that, in comparison with traditional topology of  buck-boost converter, the output filter in elementary Luo converter with inverting output significantly reduces the ripple coefficient of output voltage. It was determined that the amount of voltage ripple reduction is proportional to the product of the inductance and filter capacity values, as well as the square of the switching frequency and does not depend on the conductivity mode of the converter.